Erosive tooth wear in an asthmatic child: a case report. - dos Santos, Nicole Marchioro (2018)
Introduction: Erosive tooth wear (ETW) is defined as a mechanical chemical process that results in a cumulative loss of hard tissue without the involvement of bacteria. This process may occur in permanent and deciduous teeth and may also reach the dentin tissue. Patients who report chronic diseases, such as respiratory allergy and bronchial asthma, or recurrent acute diseases, such as tonsillitis, allergic rhinitis, sinusitis, and otitis, commonly use drugs for prolonged periods; thus, more attention should be given to the dental aspects since the drugs may cause undesirable effects. Objective: This paper aims to report and discuss a clinical case of a nine-year-old, male, Caucasian, asthmatic patient who continually uses anti-asthmatic medications and has developed ETW. Case report: According to the patient’s needs, oral hygiene instructions (use of fluoride stannous dentifrice, dental floss, and topical fluoride applications), daily use of mouthwash solution containing 0.05% sodium fluoride, and dietary guidance were recommended. Conclusion: An early and accurate diagnosis of ETW lesions and recognition of specific etiological factors allow the professional to elaborate an individualized prevention and control program for ETW progression.